Data acquisition and alert system for recirculation aquaculture system (RAS) using fog computing - Siti Maryam Zainol (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
The aim of this research is to design a data acquisition and alert system for recirculation aquaculture system (RAS) using fog computing ; to achieve the aim, the main objectives of the research are ; to design and develop a data collecting system for RAS ; to design and develop a data processing system using fog computing ; to validate data acquisition and alert system for recirculation aquaculture system using fog computing technology.